Identification and selection of elite oil palm (Elaeis guineensis Jacq.) genotypes for utilisation in a breeding program - Bhagya, H.P.; Mathur, R.K.; Ravichandran, G.; Ramajayam, D.; Babu, B. Kalyana; Anitha, P.; Murugesan, P.; Kumar, K. Sunil; Somasundaram, G.; Rahana, S.N. (Journal of Plantation Crops, 2021)
Oil palm is a vegetable oil yielding, cross-pollinated crop belonging Arecaceae family, having a high potential for increasing oil yield to fulfil the requirement of edible oil in the country. Evaluation of oil palm germplasm was carried out at ICAR-IIOPR, Pedavegi, in 73 genotypes. A correlation study reported that the height of the palm was positively correlated with height increment, rachis length, number of a leaflet, bunch number, and FFB yield. In contrast, the girth of the palm was negatively correlated with the bunch index. Two Dura genotypes viz., IC0610049-40 and IC0610051-71 with high FFB yield (276.2 and 234.6 kg palm-1 year-1, respectively) with more number of bunches palm-1 year-1 (15.3 and 16.7, respectively) and high oil to bunch ratio (20.9% for both) and one Tenera genotype IC0610049-39 with 202.5 kg FFB with 11.7 bunches palm-1 year-1 and 23.0 per cent oil to bunch ratio were selected. One low height increment Dura palm IC0610045-3 with 19.56 cm year-1 and these genotypes can be used in the future breeding program for developing mother palms for production of Tenera hybrid.